INTERVIEW: STEPHEN BURN - Stephen J., BURN (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Q: Literary history, be it national, local, or regional, is perhaps the most conservative form of literary study, with many claiming that the method is outmoded. What can literary histories do to overcome both the risk of obsolescence and their inherent conservatism? A: Near the start of Colson Whitehead’s The Underground Railroad (2016), Cora, the runaway slave, is almost captured by some opportunistic pig hunters. An untidy scuffle ensues: She was taken unawares but the moment he laid hands on her person, her blood quickened. The boy yanked Cora to the ground. She rolled over and bashed her head against a stump. He scrambled to her, pinning her. Her blood was hot. (60)